2002
DOI: 10.1046/j.1528-1157.2002.32002.x
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand Community Attitudes toward People with Epilepsy

Abstract: Summary:Purpose: International surveys on knowledge and attitudes toward people with epilepsy suggest that public opinion is improving in many countries. This study aimed to discover how New Zealand compared with other countries, and how subgroups within the New Zealand population compared with each other, by conducting a survey of community knowledge and attitudes toward epilepsy.Methods: Telephone interviews were conducted on a random sample of 400 persons older than 17 years, drawn from a midsized provincia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 10 publications
7
66
1
1
Order By: Relevance
“…It has been clearly observed that the level of education infl uences the answers about the disease and leads to less pejorative attitudes to persons with epilepsy, corroborating with other researches designed for similar purposes 4,[6][7][8][9][10][11][13][14][15] . It is inferred that populations with a lower level of education and a lower income probably also have less access to information concerning epilepsy and this contributes to maintaining erroneous concepts about the disease.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It has been clearly observed that the level of education infl uences the answers about the disease and leads to less pejorative attitudes to persons with epilepsy, corroborating with other researches designed for similar purposes 4,[6][7][8][9][10][11][13][14][15] . It is inferred that populations with a lower level of education and a lower income probably also have less access to information concerning epilepsy and this contributes to maintaining erroneous concepts about the disease.…”
Section: Discussionsupporting
confidence: 79%
“…These proportions were also observed in the study of Santos and coworkers 7 , in which the proportion of witnessing a seizure was 34% in the non-university population against 73% in the general population. Another aspect observed is that the young adults (17-30yrs) say they have witnessed more convulsive seizures than older people, a fact observed in other studies 4,11 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Community-based studies have reported that better-educated individuals offer more favorable opinions and display positive attitude (Mirnics et al, Chung; Hills and Mackenzie; Jensen and Dam). [15][16][17][18] Pharmacy students represent a better-educated section of society regarding drugs and have the potential to create awareness, improve concepts and influence attitudes towards the disease. Thus, it is important that they have the appropriate and updated knowledge and appropriate attitude towards epilepsy and antiepileptic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Sexually transmissible diseases are often considered particularly blameworthy and 'dirty' (Moore & Rosenthal, 1996;Reidpath, Brijnath, & Chan, 2005;Rosenthal & Moore, 1994). Conditions that lead to physical or cognitive disabilities which the public may consider unattractive, frightening, or related to mental retardation or mental illness, are often stigmatised (Hills & MacKenzie, 2002;Jenetette, Funk, & Murdaugh, 2005).…”
Section: Introductionmentioning
confidence: 99%